2013
DOI: 10.2106/jbjs.l.00465
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Arthroplasty and Ankle Arthrodesis

Abstract: The gait patterns of patients following three-component, mobile-bearing total ankle arthroplasty more closely resembled normal gait when compared with the gait patterns of patients following arthrodesis. Dorsal motion in the sagittal plane was primarily responsible for the differences. Improvement in self-reported clinical outcome scores was similar for both groups. Further investigation is needed to determine why patients who have undergone total ankle arthroplasty do not use the plantar flexion motion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 4 publications
3
85
1
2
Order By: Relevance
“…In our patient series mean ankle RoM as assessed with gait analysis was 17°after TAR and 12°for AAD patients. Similar ankle RoM was reported by Singer et al who concluded that dorsal ankle motion in the sagittal plane was primarily responsible for better gait patterns after TAR [17]. This slight improvement in ankle RoM after TAR also appears associated with increased knee flexion in stance compared to AAD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our patient series mean ankle RoM as assessed with gait analysis was 17°after TAR and 12°for AAD patients. Similar ankle RoM was reported by Singer et al who concluded that dorsal ankle motion in the sagittal plane was primarily responsible for better gait patterns after TAR [17]. This slight improvement in ankle RoM after TAR also appears associated with increased knee flexion in stance compared to AAD.…”
Section: Discussionsupporting
confidence: 84%
“…For joint replacement it was suggested that functional results may approximate those of healthy subjects [7], which seemed to be the most powerful arguments for the choice of an arthroplasty in comparison to an arthrodesis despite higher complication and reoperation rates [15,16]. Nevertheless, comparative studies showed that neither group functioned as well as normal subjects [8,9,11,17].…”
Section: Discussionmentioning
confidence: 99%
“…Singer reported that TAR with first-generation TAP resulted in increasingly normal gait mechanics during sagittal joint motion, which was maintained, and it also resulted in more normal ankle kinematics when compared with those following arthrodesis [24]. The gait patterns of TAR with the third-ankle prosthesis more closely resembled normal gait during sagittal plane motion and dorsiflexion, and it also resulted in a normal range of tibial tilt when compared with the gait patterns of patients following arthrodesis [24]. Peak plantar flexor moment increased in arthrodesis patients and decreased in TAR patients.…”
Section: Kinematicsmentioning
confidence: 99%
“…1 However, the overall efficacy of arthrodesis has come into question over the past decade with long-term clinical studies reporting high rates of ipsilateral hindfoot arthritis, decreased range of motion, and gait abnormalities. [1][2][3] Total ankle arthroplasty (TAA) was first introduced to the orthopedic community more than 40 years ago with the first implant systems used in the early 1970s. Progressive development in TAA punctuated by recent major advances in implant design, instrumentation, surgical technique, surgeon training, clinical and functional outcomes, and survivorship has caused a rapid growth in the popularity of TAA worldwide.…”
mentioning
confidence: 99%
“…Proposed advantages of TAA over arthrodesis include better restoration of and improvement in joint range of motion, superior gait kinematics, and decreased incidence of adjacent joint hindfoot arthritis, with equivalent pain relief and patient satisfaction. 2,6,7 However, the clinical benefits of these advantages have only recently been borne out in the literature. 5,6,8 Early first-generation permutations of TAA were infamous for high early failure rates due to non-anatomic designs, high levels of constraint (or complete lack of restraint), excessive bony resection, and gross component loosening.…”
mentioning
confidence: 99%